A CONTEXTUAL PROBLEM BASED OF LOCAL WISDOM IMPROVE THE ABILITY TO SOLVING A WORD PROBLEM MATHEMATICS STUDENTS OF ELEMENTARY SCHOOL - Riza Fatimah Zahrah; Winarti Dwi Febriani (IKIP Siliwangi, 2020)
The background of the study are the results of the study in the year 2013 that has been carried out, the capacity of finishing to solve word problems still a big the difficulties encountered by primary school student on math. First, the students was difficult to understand content from to word problems which it is served. So that it would be a much trouble, students hard to change the words of story into mathematics modelling. The purpose of this research is to had a clear grasp of concerning the improvement of the the ability for solving the word problems mathematics with is using it based math thats why chose without abandoning the local wisdom. A Contextual problem of Mathematics at class was serve in sunda language and using the game of sunda’s cultured (for example: congklak). This research used a quantitative approach with the methods quasi experiment. The experimental methods specious or quasi experiment use class experimentation and class control. Research was implemented in public primary schools 1 suganangan as a class experimentation and public primary schools 2 suganangan as a class control. Class experiment given learning with using it contextual mathematics based local with N-gain 0.51 medium category.